Effectiveness of Distance Learning Technologies in Higher Education in Canada - Thompson, Amelia (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the effectiveness of distance learning technologies in higher education in Canada. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Distance learning technologies in Canadian higher education have significantly expanded access to education, particularly for remote communities. They offer diverse courses and programs, accommodating non-traditional students and professionals. These technologies facilitate interactive learning, promoting collaboration among students and instructors. Studies demonstrate comparable learning outcomes between online and traditional classroom settings. Overall, integrating distance learning technologies has enhanced accessibility, flexibility, and quality of education in Canada. Unique Contribution to Theory, Practice and Policy: Social cognitive theory, diffusion of innovations theory & community of inquiry framework may be used to anchor future studies on the effectiveness of distance learning technologies in higher education in Canada. Encourage universities and colleges to invest in professional development programs for instructors to enhance their pedagogical skills in utilizing distance learning technologies effectively. Advocate for policy initiatives that support equitable access to distance learning technologies and resources for all students, regardless of their geographical location or socio-economic background.